PENGEMBANGAN KOMPETENSI PEDAGOGIK GURU PENDIDIKAN AGAMA ISLAM DI MADRASAH (Studi Kasus di MIN Malang I) - Ahmad Fatah Yasin (El-QUDWAH, 2011)
This research comes from a thoughtfulness of any problems about developing competence of pedagogic teacher in MIN Malang. This research tried to answer problems about developing competence of pedagogic of Islamic teacher doing in MIN Malang 1, and also the positive implication into the increasing of learning quality. The developing competence of pedagogic that was done are: (a) arranging developing planning based on teacher evaluation, (b) doing developing competence of pedagogic through any activities and research of PTK, aim to increase the teachers mutual in learning management, (c) increasing effort, done by government, islam school and especially the teachers indeed. The developing competence of pedagogic of Islamic teachers in MIN Malang 1 implicate positive to the increasing of quality in learning, this was signed by the indicators: a. there is reparation of learning process  appropriate with demand of modern learning world, b. there is reparation of teacher mutual in learning so implicate to the mutual/ achievement the studying result of students, both academic and non-academic.Key words: developing, pedagogic competence, islamic teacher, MIN Malang 1